PERILAKU KEAGAMAAN KAUM WARIA YOGYAKARTA; Kasus di Pondok Pesantren Waria “Senin-Kemis” Yogyakarta - Imam Machali (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2011)
Religious behavior of Transgender in Yogyakarta, especially in Islamic boarding schools ofTransgender “Monday-Thursday” has five dimensions: Religious Beliefs (Ideological) ReligiousPractices (ritualistic), Religious Experience (consequential), religious comprehension(experiential), and Religious knowledge (Intellectual). Religious behavior of transgender isinfluenced by two factors: internal and external factors. The internal factor is the factor ofpsychology, physiology, knowledge, and experience. Psychological and physiological factorsare the cause of the transsexual character of an individual. External factors are a family,couples, social, economics, and politics. The factors shape and influence of “typical” religiouspractice of transgender in the Islamic boarding school “Monday-Thursday” Yogyakarta.